Underwater equal-latency contours of a harbor porpoise (Phocoena phocoena) for tonal signals between 0.5 and 125 kHz - Wensveen, Paul Jacobus; Huijser, Léonie A E; Hoek, Lean; Kastelein, Ronald A. (Springer, 2016)
Loudness perception can be studied based on the assumption that sounds of equal loudness elicit equal reaction time (RT; or “response latency”). We measured the underwater RTs of a harbor porpoise to narrowband frequency-modulated sounds and constructed six equal-latency contours. The contours paralleled the audiogram at low sensation levels (high RTs). At high-sensation levels, contours flattened between 0.5 and 31.5 kHz but dropped substantially (RTs shortened) beyond those frequencies. This study suggests that equal-latency-based frequency weighting can emulate noise perception in porpoises for low and middle frequencies but that the RT-loudness correlation is relatively weak for very high frequencies.